Determination of Mechanical Properties of Aged Wood Material Using Vickers Microhardness Test - AŞIKUZUN, Elif; KARAGÖZ İŞLEYEN, Ümmü (Kastamonu University, 2019)
Aim of study: In this study, it was aimed to determine the changes under the influence of time of the age wood obtained from the historical wooden buildings.Area of study: The aged wood (AW) and new wood (NW) were used in experimental analysis. Wood samples were Pinus sylvestris L. The aged wood was over 50 years old and is derived from the historical wooden buildings in Kastamonu, Turkey.Material and Methods: The aged and new wood samples were prepared to compare the effect of time. The mechanical properties, crystallinity and microstructure of new and aged wood were investigated by using Vickers microhardness tester, XRD and SEM, respectively. The change in the mechanical and structural properties of the aged and new wood material was determined.Main results: The microhardness values depended on the applied load and increased with increasing the applied load. Meyer's law, Proportional Sample Resistance, Elastic/Plastic Deformation, Hays-Kendall Approach and Indentation-Induced Cracking models were analyzed for investigation of load independent microhardness values. As a result, IIC model was the most successful model.Research highlights: It is very important to know the changes that wood has suffered in time in order to conservation of wooden cultural heritage objects and reuse of aged wood.Keywords: Aged wood, new wood, historical construction, cultural heritage,